Innovative strategies for implementing FinTech in banking - Albastaki, Yousif, 1962-; Razzaque, Anjum, 1973-; Sarea, Adel M., 1979- (Business Science Reference, 2020)
""This book addresses key issues, challenges, opportunities, and implementation of FinTech in the banking sector"--Provided by publisher"--